The contribution of cultural values to education in the Mangupa-upa tradition of the Batak Mandailing community - Nasution, Aura Diah Meitasari (Universitas Riau Kepulauan, 2025)
This research is motivated by the importance of preserving cultural values in the Mangupa-upa tradition of the Mandailing Batak people, which has religious, social, and moral significance. The problem addressed in this research is how Mandailing cultural values are reflected in the Mangupa-upa tradition. The purpose of this research is to describe and analyze the cultural values in the Mangupa-upa ceremony in relation to Koentjaraningrat's cultural elements theory. This research uses a descriptive qualitative approach with observation, documentation, and literature study techniques on the implementation of Mangupa-upa. The results of the research indicate that the Mangupa-upa tradition encompasses five cultural elements: the religious system, social organization, knowledge system, language, and arts.